The associations of early specialization, sports volume, and maturity status with musculoskeletal injury in elite youth football players - Li, X.; Feng, R.; Luo, S.; Li, C.; Gomez-Ruano, M. A. (Frontiers in Physiology, 2023)
Background: Youth football in schools has experienced rapid growth in China. Despite the increase of players engaging in more frequent, intensive, and organized sports training at their early ages, the controversy over early specialization (ES) still exists. This study aims to: a) investigate the training situation of players in the Chinese School Football Programme and b) examine the associations of early specialization, sports volume, and maturity status with musculoskeletal injury.